Programmer's guide to the EGA, VGA, and Super VGA cards - Ferraro, Richard F. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1994)
A guide to industry graphics standards for personal computers that explains various PC graphics environments and graphics programming principles. The author discusses the features and operations of the Super VGA, VGA, XGA, 8514/A, and EGA graphics standards and tutors the reader on how to write programs that support and take advantage of the popular chip sets and graphics boards supporting those standards. Annotation copyright Book News, Inc. Portland, Or.
Ch. 1. Introduction to the Programmer's Guide -- Ch. 2. The EGA, VGA, and Super VGA Features -- Ch. 3. Graphics Hardware and Software -- Ch. 4. Types of Graphics Systems -- Ch. 5. Principles of Computer Graphics -- Ch. 6. Alphanumeric Processing -- Ch. 7. Graphics Processing -- Ch. 8. Color Palette and Color Registers -- Ch. 9. Reading the State of the EGA and VGA -- Ch. 10. The EGA/VGA Registers -- Ch. 11. The EGA/VGA BIOS -- Ch. 12. Programming Examples -- Ch. 13. The Super VGA -- Ch. 14. Graphics Coprocessors -- Ch. 15. Super VGA Code Basics -- Ch. 16. The Adapter Interface (AI) -- Ch. 17. The 8514/A -- Ch. 18. The XGA -- Ch. 19. ATI Technologies -- Ch. 20. Chips and Technologies -- Ch. 21. Cirrus Logic -- Ch. 22. The Video7 Super VGA Chip Sets -- Ch. 23. IIT -- Ch. 24. NCR -- Ch. 25. Oak -- Ch. 26. S3 Incorporated -- Ch. 27. The Trident Super VGA Chip Sets -- Ch. 28. The Tseng Labs Super VGA Chips -- Ch. 29. The Paradise Super VGA Chips -- Ch. 30. Weitek.
Includes index.
Keywords: IBM PERSONAL COMPUTER PROGRAMMING